2023
DOI: 10.3389/fpubh.2023.1134076
|View full text |Cite
|
Sign up to set email alerts
|

“Something very taboo”: a qualitative exploration of beliefs, barriers, and recommendations for improving mental health care and access for Hispanic adults in the Paso del Norte U.S.-Mexico border region

Jason Mallonee,
Rosa Escalante,
Eden Hernandez Robles
et al.

Abstract: BackgroundHispanic adults with mental health conditions in the United States experience disproportionate access to and utilization of professional mental health treatment. This is believed to be in part due to systemic barriers and challenges, difficulty accessing care, cultural factors, and stigma. Studies to date have failed to examine these specific factors within the unique context of the Paso del Norte U.S.-Mexico border region.MethodsFor this study, 25 Hispanic adults identifying primarily of Mexican des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Regarding marital status, our findings found that farmers who were single or married had higher HL scores than widows or divorcees. It is possible that individuals who were widowed or divorced had a lack of motivation to attend to things related to health education due to psychological, spiritual, and economical issues ( 35 ). Another possibility is that other family members may support and compensate individuals to achieve health-related tasks ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding marital status, our findings found that farmers who were single or married had higher HL scores than widows or divorcees. It is possible that individuals who were widowed or divorced had a lack of motivation to attend to things related to health education due to psychological, spiritual, and economical issues ( 35 ). Another possibility is that other family members may support and compensate individuals to achieve health-related tasks ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%